PENGARUH MINAT PERILAKU BERWIRAUSAHA SEBAGAI VARIABEL MEDIASI DALAM PENGEMBANGAN THEORY OF PLANNED BEHAVIOR: (Studi Kasus : Masyarakat yang berwirausaha di Kota Medan) - Simanihuruk, Peran; Tamba, Darwis; Sagala, Roslinda; Sinaga, Ria Veronica; Simangunsong, Elisabeth (UNIKA Santo Thomas, 2025)
This study aims to analyze the role of entrepreneurial behavioral intention as a mediating variable in the development of the Theory of Planned Behavior. The research was conducted in Medan City, with a population consisting of individuals engaged in entrepreneurship within the city. The sample of the study included 400 respondents randomly selected from the population. Data collection was carried out through questionnaires and documentation, while data analysis was performed using Smart PLS version 4.0. The results of the study show that attitude toward entrepreneurial behavior has a significant positive effect on entrepreneurial intention (t-statistic 3.584 > 1.96; p-value 0.000) as well as on entrepreneurial behavior (t-statistic 3.006 > 1.96; p-value 0.003). Subjective norms from reference groups also have a significant positive effect on entrepreneurial intention (t-statistic 2.139 > 1.96; p-value 0.032) and entrepreneurial behavior (t-statistic 2.031 > 1.96; p-value 0.042). Perceived behavioral control has a significant positive effect on entrepreneurial intention (t-statistic 4.043 > 1.96; p-value 0.000) and entrepreneurial behavior (t-statistic 11.194 > 1.96; p-value 0.000). Self-confidence positively influences entrepreneurial intention (t-statistic 4.825 > 1.96; p-value 0.000), but does not have a significant effect on entrepreneurial behavior (t-statistic 0.168 < 1.96; p-value 0.867). Entrepreneurial intention has a positive effect on entrepreneurial behavior (t-statistic 2.576 > 1.96; p-value 0.010). Entrepreneurial intention was found to significantly mediate the influence of entrepreneurial attitude on entrepreneurial behavior (t-statistic 2.060 > 1.96; p-value 0.039). However, entrepreneurial intention does not mediate the influence of subjective norms on entrepreneurial behavior significantly (t-statistic 1.578 < 1.96; p-value 0.115). Similarly, entrepreneurial intention does not significantly mediate the influence of perceived behavioral control on entrepreneurial behavior (t-statistic 1.925 < 1.96; p-value 0.054). On the other hand, entrepreneurial intention significantly mediates the influence of self-confidence on entrepreneurial behavior (t-statistic 2.326 > 1.96; p-value 0.020). To enhance entrepreneurial intention and behavior, synergy between education, industry, and society is necessary to create an environment that supports entrepreneurship. Training programs that combine business simulations, mentoring, and confidence-building can help foster a positive entrepreneurial attitude. Additionally, social support from family, friends, and entrepreneur communities, as well as access to capital and supportive regulations, are crucial to optimizing individual potential for sustainable entrepreneurship.